Identificación del agente causal de infección vaginal y su relación con los factores de riesgo en mujeres de edad fértil que acuden al Hospital Kokichi Otani de la parroquia Vilcabamba - Toledo Parra, Alfredo Naun (2013)
The vaginal infections are presented with more frequency in the reproductive stage, being cause of gynecological consultation. They are given when there are a contamination or imbalance of the normal vaginal ecosystem (Lactobacillus), which protects to the mucous one in front of the establishment of microorganisms patógenos, según Surveillance General Epidemiológica/Dirección of Epidemiology / SSA, more than 90% of the vulvovaginitis has as agent etiológico the Gardnerella vaginalis, yeasts and Trichomona vaginalis; the same ones that are not exception in the study area, reason for which the present investigation was executed, with the objective of to identify the main causal agent of vaginal infection in women in fertile age and to determine factors of risk, by means of a study of descriptive type, of traverse court whose study population conformed it 55 women of external consultation that fulfilled the inclusion approaches. The study was carried out by means of analysis laboratorial of vaginal secretion in fresh, coloration of Gram, aminas test and KOH (20%). a survey was Also applied to identify some factors of risk, reaching the following conclusions that, Gardnerella Vaginalis was the most frequent agent with 61%, followed by yeasts with 24%, and mixed infections with a 11%(Gardnerella vaginalis and yeasts) and Trichomona vaginalis with 5%. Among the factors of risk the sexual activity prevails in 65%; use of adjusted pants for times lingering 64%: use of synthetic intimate clothes and of lycra in 44% and 55% for the soap use perfumed for the genital toilet. Key words: Vaginal infections, Gardnerella vaginalis, Trichomona vaginalis, mixed infections.